Down the black hole: Sustaining national socio-technical imaginaries of coal in Poland. (July 2018) - Kuchler, Magdalena; Bridge, Gavin
Abstract: This paper explores the socio-technical imaginaries surrounding infrastructures of coal mining and coal combustion in Poland. Contemporary policy makers in Poland mobilise a national imaginary inherited from communist times – encapsulated in the slogan 'Poland stands on coal' – that fuses infrastructures of coal extraction and combustion with the fate of the nation. This socio-technical imaginary provides support for coal futures, even in the face of contradictory evidence for domestic resource depletion, poor regional air quality, and global climate change. To examine this process, the paper brings research on socio-technical imaginaries into conversation with work on resource materialities. It highlights how certain materialities of coal (abundance, accessibility, energy density, location) were integral to the emergence of a national socio-technical imaginary of modernisation via coal; and how other materialities (declining resource quality, effects of emissions on respiratory health, coal as CO2 -in-waiting) now collide with the political strategies of a government determined to reassert 'black gold' as a bedrock of national development for years to come. The paper considers how contemporary political efforts to rehabilitate coal and secure its future in Poland draw selectively upon a socio-technical imaginary of coal-fuelled national modernisation.